Occurrence and multilocus genotyping of Giardia duodenalis in black-boned sheep and goats in southwestern China - Dan Chen (Parasites & Vectors, 2019)
Abstract Background Giardia duodenalis is an important intestinal protozoan infecting both humans and animals, causing significant public health concern and immeasurable economic losses to animal husbandry. Sheep and goats have been reported as common reservoirs of G. duodenalis, but only a limited amount of information is available for native breeds of these small ruminants in China. The present study investigated the prevalence and multilocus genotypes of G. duodenalis in black-boned sheep and goats, two important native breeds in Yunnan Province, southwestern China. Methods Fecal samples were collected from 336 black-boned goats and 325 black-boned sheep from five counties (Meishui, Shanshu, Shilin, Yongsheng and Nanping) of Yunnan Province and the genomic DNA was extracted from these feces. The prevalence of G. duodenalis was determined by the nested PCR targeting the β-giardin (bg) gene. The assemblages and multilocus genotypes (MLGs) were investigated based on analyses of three genetic loci, i.e. bg, glutamate dehydrogenase (gdh) and triosephosphate isomerase (tpi). Results Giardia duodenalis infection was detected in both black-boned sheep and goats, and the prevalence of G. duodenalis in black-boned sheep (21.8%, 71/325) was significantly higher (χ 2 = 36.63, df = 1, P < 0.001) than that in black-boned goats (4.8%, 16/336). Significant differences in prevalence were also observed in goats and sheep from different counties (χ 2 = 39.83, df = 4, P < 0.001) and age groups (χ 2 = 97.33, df = 3, P < 0.001). Zoonotic assemblage A and animal-specific assemblage E were identified in both black-boned sheep and goats with the latter as the predominant assemblage. Based on sequences obtained from the three genetic loci (bg, gdh and tpi), 16 MLGs were obtained in black-boned sheep and goats, including 15 MLGs in assemblage E and one MLG in assemblage A. Conclusions Our results not only extended the host range of G. duodenalis, but also revealed high genetic variations in G. duodenalis assemblages. The findings of the present study also provide baseline data for preventing and controlling G. duodenalis infection in black-boned sheep and goats in Yunnan Province.